The Role of The Human Development Index in Improving The Effectiveness of Social Budget to Achieve Sustainable Development Goals 11 - Amanda Bulan Junia Baginda; Andi Chairil Furqan; Selmita Paranoan (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
This study utilizes secondary data from 532 provincial, district, and city governments in Indonesia from 2021 to 2022, with a total of 1,064 observations. Data sources come from the Ministry of Finance, Statistics Indonesia (BPS), and Bappenas. The analysis results indicate that the social function budget has not had a significant direct impact on reducing the proportion of the population living in inadequate housing. However, when the interaction with the HDI is taken into account, the effect of the social function budget on the achievement of SDG 11 becomes significant and positive. These findings indicate that the quality of human development plays a crucial role in increasing the effectiveness of social budget utilization. Therefore, this study recommends integrating social budget policies and strategies to improve the HDI so that the development of adequate cities and human settlements can be achieved sustainably. Regional governments are expected to develop inclusive budget plans and encourage investment in the education, health, and community economic sectors to increase the success of social programs in supporting the achievement of the SDGs.